Microsite-Based Mathematical Statistics Educational Media to Increase Student Study Motivation after the Covid-19 Pandemic - Nurfalah, Edy; Rahayu, Puji (Universitas Negeri Surabaya, 2023)
This research aims to describe student study motivation in learning mathematical statistics using microsite-based media after the Covid-19 pandemic. The research methodology used is descriptive quantitative about student study motivation using six indicators from Pintrich [1] after researching the development of microsite-based media with the research and development method and implemented in mathematical statistics lectures. By using microsite-based educational media, student study motivation in terms of the six indicators produced is in the very strong category with an average percent score reaching 80%.